"PANGGIH " ARTIST ART CRAFT WOVEN “PECI” FROM BANANA TREE FRONDS - Irawan Sukma (JURNAL PAKARENA, 2022)
Panggih is one of the woven craft artists who are already famous in East OKU Regency because of his peculiarity in making works in the form of "Peci from banana tree fronds". Not only in the district environment, h work is sold, but there are also many orders from outside the city and even the province. ina intends to develop craft art in Belitang, so that cra artworks are not extinct and there are future generations. The purpose of this research is to reflect on and introduce how the figure of a 'Panggih' works in the world of Fine Arts. This research is qualitative, describing how a woven craft artist named Panggih creativity, made artwork based o banana tree fronds. Furthermore, this research tells how panggih's creative process becomes a craft artist? What craft artwork was created by Pangg and the specialty of the artwork created by Panggih? And how is t process of making the craft artwork "Peci" by Panggih? This is what w be explained in this study. Wallas's theoretical thoughts about the creative process, combined with Anna Cra  thoughts on the circle of creative processes were used in this research. It is hoped that the results of this study can foster the interest and talent of the younger generation in East OKU and be able to pass on what has been done by Panggih so that the Kriya A made from banana tree fronds becomes a strong identity for Panggih work for the East OKU Community.